Determination of physical properties of undisturbed soil samples according to V. Novák - Marko Spasić; Oldřich Vacek; Kateřina Vejvodová; Václav Tejnecký; Filip Polák; Luboš Borůvka; Ondřej Drábek (MethodsX, 2023)
The methodology described here presents the procedures for determining physical soil properties of undisturbed soil samples. Besides describing the methods for determining bulk and particle density, moisture content and porosity of the soil in detail, it also offers a way of determining soil's water holding properties when there is no pressure membrane apparatus available. This method is based on a capillary water saturation experiment and gravimetric measurements performed in different time intervals after the saturation (30 minutes, 2 hours, and 24 hours). With a few, simple to follow steps, and not using complicated and space-consuming equipment, it can be replicated in almost any laboratory, and the results are easily interpreted. The method was, and still is, widely used in the Czech Republic, and some parts of it are used as standard soil testing methods. To a lesser or greater detail, this method is described in Rejšek (1999), Valla et al. (2011), Pospíšilová et al. (2016) and ÚKZÚZ (2016), and this methodology is compiled from those publications, mainly focusing (and using the same abbreviations) on the procedures described by Valla et al. (2011). The methodology described does not essentially differ from the original, but the steps here have been described to a greater detail, based on the practical experiences obtained over the years, in order to make some common mistakes less likely to happen. The methodology is further complemented with graphical illustrations for each step described in the process, making it clearer, more easily understood, and easier to replicate. Since this methodology has not been available in English so far, this guide offers a great opportunity of its replication on an international level. • Simple, cost-effective and environmentally friendly method for determining physical soil properties • Easy replication and results interpretation • Results can be obtained even in non-highly specialized soil laboratories